(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The study investigated the physicochemical properties of starches from Caladium bicolor (wild cocoyam), Icacina trichantha (false yam), dioscorea villosa (wild sweet yam) and oyster mushroom. Amylose/amylopectin ratio, gel characteristics, hygroscopicity among other properties were examined. The study revealed that wild yam, sweet yam, false yam and oyster mushroom have total starch content of 86.6%, 82.8%, 58.4& and 49.3% respectively. False yam and oyster mushroom had high percentages of amylose (40.2 and 56.7%) while wild cocoyam and sweet yam had high amylopectin content (88.9% and 84.6%) respectively. The functional properties of the starch samples compared favourably with starches from edible sources. This study revealed that starches from non-edible sources like wild cocoyam, false yam, mushroom and sweet yam can be used in the synthesis of bioplastics with improved quality. This will reduce the amount of plastics littered in landfills and will also replace the use of edible starches in non-food purposes enabling edible starches to be available for human consumption and other food/medical applications.